Potential negative effects of the Brazilian Space Program on coastal sharks - Wosnick, Natascha; Chaves, Ana Paula; Leite, Renata Daldin; Nunes, Jorge Luiz Silva; Hauser-Davis, Rachel Ann (Frontiers in Marine Science, 2023)
The Brazilian government recently announced its first partnerships with the private sector, including American and Canadian companies, to use the Alcântara Space Center (Maranhão, northern Brazil). This center is known for its privileged location, saving up to 30% of fuel in launches. Its operationalization is an offshoot of the Technological Safeguards Agreement, which is important for the Brazilian Space Program due to greater space sector investments and environmentally relevant projects. In 2003, a major fire at the Alcântara Space Center destroyed a rocket and killed 21 workers, halting Brazilian Space Program activities. Recently, our research group reported serious environmental consequences of this accident, i.e., extremely high amounts of Rubidium (Rb) in apex predatory sharks near the Alcântara Space Center. This element is used in fuels and in space propulsion systems and is potentially toxic, displaying bioaccumulating and biomagnifying capabilities. The observed concentrations are the highest ever detected in any living organism (up to 24.65 mg kg-1 dry weight). The launch base is located on the Brazilian Amazon Coast, and population recruitment impacts may compromise biota conservation and biodiversity. Local shark meat consumption is also worrying, as consumers may be exposed to Rb, whose effects in humans are unknown. We, therefore, indicate an urgent need for biomonitoring efforts in the area, as the Alcântara Space Center is about to operate at its maximum capacity.